Mathematical Model for The Transmission of Malaria In Uganda. - Lusambya, Robert (Kabale University, 2024)
The resent an ordinary differential equation mathematical model for the spread of malaria in Mosquito populations. Susceptible humans can be infected when they are bitten by an infectious Mosquito. They then progress through the infectious and asymptomatic classes, before -entering the susceptible class. Susceptible Mosquitoes can become infected when they bite infectious and asymptomatic humans, and once infected they move through infectious class. The c reproduction number RO is established and used to determine whether the disease dies out or persists in the population. We show that given RO <1, the disease-free equilibrium is globally asymptotically stable and the disease always dies out and if RO > 1, there exists a unique e:::c=mic equilibrium which is globally stable and the disease persists.